Analisis Risisko Musculoskeletal Disorders Pekerja Harian Lepas dengan Metode Rapid Entire Body Assesment (REBA) di PT Arum Berlian Utama Jember - Intan Normania; Rusindiyanto Rusindiyanto (Universitas Batanghari Jambi, 2023)
Complaints or musculoskeletal disorders (MSDs) are a phenomenon that is often experienced by workers who handle materials manually. PT Arum Berlian Utama is a company operating in the construction sector. It cannot be denied that companies operating in the construction sector definitely carry out work that handles materials manually, such as the construction of houses by PT Arum Berlian Utama at Walisongo Residence. This study aims to determine the level of potential risk of musculoskeletal disorders in casual daily workers using the Rapid Entire Body Assessment (REBA) method. Work process observations and interviews were carried out in March 2023 using the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM). Most workers experience complaints in the left shoulder, right shoulder, right wrist, right upper arm, right thigh, left thigh, lower back. The research results showed that 4 (four) casual daily workers had a high risk of MSDs and 6 (six) casual daily workers had a very high risk of MSDs. Proposed improvements can be made by improving work posture by avoiding postures that are too bent and folding body parts for too long as well as stretching between work hours and regular exercise to prevent and reduce the risk of dangerous ergonomic factors.